Impact of Attachment Between Mother and Child on Controlling Aggressive Behavior in Early Childhood - Fanny Meisya Hasanah; Ika Ariyati; Aprezo Pardodi Maba (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
Aggressive behavior in children is one of the behaviors that requires primary attention in children's education and care, because this behavior can endanger the child and those around him. However, this behavior can be controlled by parents, namely by providing attachment or emotional ties to the child. This research aims to determine the influence and role of attachment between children and mothers in controlling aggressive behavior in early childhood at RA Muslimat NU 1 Tulusrejo. This research method uses simple linear regression analysis with a quantitative approach involving 85 samples consisting of mothers of RA Muslimat NU 1 Tulusrejo students. Sampling using techniques of simple random sampling. This research shows a coefficient of determination value of 0.237 with a significance level (p) of 0.000 (p < 0.05) and a correlation of (-0.487). The results of the study show that there is a negative relationship between attachment between child and mother and aggressive behavior in early childhood. This means that the stronger the level of attachment between child and mother, the lower the aggressive behavior in early childhood, especially at RA Muslimat NU 1 Tulusrejo. So it can be concluded that there is an influence of attachment between child and mother in controlling aggressive behavior in early childhood at RA Muslimat NU 1 Tulusrejo. This research highlights the importance of early relationship experiences and quality of parenting in preventing or reducing aggressive behavior in early childhood, focusing on the role of attachment between child and mother in controlling aggressive behavior through the formation of emotional bonds from an early age by emphasizing the importance of intervention at the child's developmental stage